CONCEPTUAL ASPECTS OF RESEARCHING THE PROBLEM OF CYBER SECURITY - Uygun R. Turdiev (International Scientific and Current Research Conferences, 2023)
This article analyzes the conceptual aspects of the study of cybersecurity problems. In particular, the content of the concept of cybersecurity, problems in this area, and the reasons for their occurrence are disclosed. Also, this article highlights the reforms in the Republic of Uzbekistan to ensure cybersecurity, regulatory frameworks, and participation in international rankings.